2012
DOI: 10.1186/1756-0500-5-681
|View full text |Cite
|
Sign up to set email alerts
|

Common bile duct adenocarcinoma in a patient with situs inversus totalis: report of a rare case

Abstract: BackgroundSitus inversus totalis represents an unusual anomaly characterized by a mirror-image transposition of the abdominal and thoracic viscera. It often occurs concomitantly with other disorders that make difficult diagnosis and management of abdominal pathology. The relationship between situs inversus totalis and cancer remains unclear.Case presentationWe describe a 33-year old Guinean man with situs inversus totalis who presented with obstructive jaundice. Imaging and endoscopic modalities demonstrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 20 publications
0
25
0
8
Order By: Relevance
“…Eine besondere maligne Prädisposi-tion wird den verschiedenen Formen des Situs inversus nicht zugeschrieben [1]. Gleichwohl findet sich in der Literatur eine Reihe von Fallberichten, die sich speziell mit der Situation von diagnostischen und therapeutischen Eingriffen beim Zusammentreffen von Situs inversus mit malignen Prozessen im Bereich der Gallenwege bzw.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Eine besondere maligne Prädisposi-tion wird den verschiedenen Formen des Situs inversus nicht zugeschrieben [1]. Gleichwohl findet sich in der Literatur eine Reihe von Fallberichten, die sich speziell mit der Situation von diagnostischen und therapeutischen Eingriffen beim Zusammentreffen von Situs inversus mit malignen Prozessen im Bereich der Gallenwege bzw.…”
Section: Diskussionunclassified
“…Bei den in der Weltliteratur bislang publizierten ca. 40 Fällen derartiger peripapillärer Malignome handelte es sich ausschließlich um Patienten mit einem Situs inversus totalis oder ambiguus [1,2]. Ein Situs inversus partialis taucht in der Weltliteratur im operativen Zusammenhang bislang nur in 2 Einzelfallberichten auf, die sich mit einer Cholezystektomie bei Cholezystitis befassen und einem weiteren Bericht zur Durchführung einer ERCP in dieser Situation [4,5,7] Hinsichtlich der präoperativen Abklärung hat sich wiederum die qualitativ hochwertige CT bewährt, da sie eine plastische Darstellung der ungewöhn-lichen anatomischen Situation und damit die Antizipation spezieller intraoperativer Herausforderungen ermöglich-te (.…”
Section: Diskussionunclassified
“…Previous authors have reported performing pancreaticoduodenectomy in patients with SI or SIT [10-15]. They reported that the surgical procedures were difficult because of the anatomical abnormalities and that special attention should be paid to diagnosis and preoperative staging.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the individuals with SIT are asymptomatic and are detected accidently at the time of clinical examination and radiological investigations for some other condition. It is not considered to predispose to cancers; however, rare cases of malignancies of lung 3 , stomach 4 , liver 4 , common bile duct 5 , colon 6 , rectum 7 , kidney 8 and gastric lymphoma 9 have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%